(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
The project about the Toponymy of Quindio is a structured attempt for establishing the toponymic corpus and the linguistic, historic and cultural motivation of the processes of nomination in the area of La Hoya of Quindio River (Colombia), since its historical origins until now. In order to do so, different types of toponyms are studied, in accordance with the taxonomy of Camps and Noroña (1989), and the possible motivations areestablished based on the most trustworthy sources and the speakers’ perception. The purpose is to answer two questions: what motivated the colonists and founders to give a particular name to the different places in the territory? What ideological components from diverse traditions are hidden in those motivations? This partial report shows the general results of the project and the methodology for data analysis.